EKSPLORASI TEKNIK FACE DAN BODY PAINTING UNTUK MENAMBAH ARTISTIK PAGELARAN BATIK FASHION ART WEAR - Syamsiar, S., (Institut Seni Indoensia Surakarta, 2018)
ABSTRACTThis artistic research is conducted to explore face and body painting techniques. Its application to the model in fashion batik fashion show. Face painting is a painting that only uses the face as a medium (the field to be painted), while the body painting medium is the whole body from the neck to the feet. The creation process model refers to contemporary art in which art barriers are not limited to a combination of face and body painting, batik fashion art wear, dance art and music art, which is packaged in the form of a fashion show. Kind of batik fashion art wear is selected batik carnival fashion, glamorous batik fashion, Fashion Batik Klasic and fashion batik casual. The four forms of fashion batik is chosen because it is often displayed in the event of a major fashion show in the city of Solo.Creation methods include Exploration (Observation, exploration of objects and the subject of creation), Improvisation (Experiments to make sketches of face design and body painting), Embodiments (creation of works and Fashion show performances). Creation of the work of face and body painting is expected to be able to produce artwork face and body painting the right model used in batik fashion art wear fashion, and able to add artistic batik fashion art fashion wear.Â Keywords: Face painting, body painting, fashion, batik, artistic, art wear.